Recombinant Human Collagen XV Regulates Cell Adhesion and Migration - Hurskainen, Merja (American Society for Biochemistry and Molecular Biology, 2010)
The C-terminal end of collagen XV, restin, has been the focus of several studies, but the functions of full-length collagen XV have remained unknown. We describe here studies on the production, purification, and function of collagen XV and the production of a monoclonal N-terminal antibody to it. Full-length human collagen XV was produced in insect cells using baculoviruses and purified from the cell culture medium. The yield was 15 mg/liter of cell culture medium. The collagen XV was shown to be trimeric, with disulfide bonds in the collagenous region. Rotary shadowing electron microscopy revealed rod-like molecules with a mean length of 241.8 nm and with a globular domain at one end. The globular domain was verified to be the N-terminal end by N-terminal antibody binding. The molecules show flexibility in their conformation, presumably due to the many interruptions in their collagenous domains. The ability of collagen XV to serve as a substrate for cells was tested in cell adhesion assays, and it was shown that cells did not bind to collagen XV-coated surfaces. When added to the culture medium of fibroblasts and fibrosarcoma cells, however, collagen XV rapidly bound to their fibronectin network. Solid phase assays showed that collagen XV binds to fibronectin, laminin, and vitronectin and that it binds to the collagen/gelatin-binding domain of fibronectin. No binding was detected to fibrillar collagens, fibril-associated collagens, or decorin. Interestingly, collagen XV was found to inhibit the adhesion and migration of fibrosarcoma cells when present in fibronectin-containing matrices.